Fakir - "Bharucha, Ruzbeh N" (New Delhi, 2010)
The One who makes the thunder roar, also hears a butterfly sigh. A hippie with an inclination for suicide, a fakir with a quaint sense of humour, a journey that might change your life forever... The Fakir, is a breathtaking spiritual odyssey to your inner self, where God and Master dwell. Experience the joy of being alive, learn the simple yet life altering philosophy of compassion towards all and heal yourself by taking that first step towards CHANGE. A fascinating story that explores complex issues in a simple, very easy - to - understand, accessible way - karma, divine action, life after death, spirit communication, the power of prayer, faith and forgiveness, energy and healing; the search for God in goodness and most importantly being constantly attuned with your Master. The Fakir, shows you not only how to live but also how to die.
Keywords: Mind